Insects associated with a shaded coffee agroecosystem in Milpuc, Amazonas, Peru (UNED Research Journal, 2020)
Introduction: Coffee agroecosystems serve as refuge to some species, favoring biodiversity, but studies in the Amazon region are scarce. Objective: To quantify insects in three vertical levels in coffee plants under shade. Methods: From June to October 2018 we collected insects in the low, medium and high strata of ten coffee plants, every 15 days, with aerial insect net, aspirator and pitfall traps. Results: 1 923 specimens belonging to eight orders, 35 families and 40 genera were collected. Hemiptera had the most families (9) and genera (13). Coleoptera were most abundance (28% of specimens). The dominant genera were Apis and Canthon, both with 108 individuals. The highest richness, abundance and diversity were recorded in the middle stratum, with 35 species, 756 individuals and with total species diversity index 1D = 28,5, and abundant species diversity index 2D=25,56. The maximum abundance of insects coincides with high humidity and precipitation, and low temperature. The accumulation curve stabilized from sample five. Conclusion: This particular Amazon agroecosystem harbors a considerable biodiversity of insects.
Keywords: Amazonas; Diversity; Insects; Fluctuation; Abundance; Coffee